Strengthening Public Service Motivation with Spiritual Leadership: An empirical Study of Public Organizations in East Java - Indra Risni Utami; Ricky Adi Putranto; Iin Agustina (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This study aims to examine the important role of each aspect of spiritual leadership (which consist of vision, hope or belief, and altruistic love) on the public service motivation (PSM) among employees who work in public organizations in East Java Province. As many as 72 civil servants who were involved as respondents in this study identified who worked in public organizations in the province of East Java. Data that has been collected were investigated using multiple regression analysis to answer research questions about what aspects of spiritual leadership have the most influence on PSM. The findings of this study reveal that among three aspects of spiritual leadership only two aspects that are hope or faith and altruistic love were found to have a significant effect on PSM. The vision which considered one dimension of spiritual leadership was found not to be significant in strengthening PSM. The value of the coefficient of determination shows a sufficient variety of variants from the aspect of spiritual leadership as a determinant of PSM.